Evaluation of multistep derivatization methods for identification and quantification of oxygenated species in organic aerosol - FLORES RANGEL, ROSA MARIA (Elsevier, 2015)
Two, 3-step methods for derivatizing mono- and multi-functional species with carbonyl (CO), carboxylic acid (-COOH), and alcohol (-OH) moieties were compared and optimized. In Method 1, the CO, -COOH, and -OH moieties were converted (1) to methyloximes (R-CN-OCH3) with O-methylhydroxylamine hydrochloride (MHA), (2) to methyl esters (OC-R-OCH3) with (trimethylsilyl)diazomethane in methanol (TMSD/MeOH), and (3) to trimethylsilyl ethers [R-OSi(CH3)3] with N,O-bis(trimethylsilyl)-trifluoroacetamide (BSTFA) containing 1% trimethylchlorosilane (TMCS), respectively. Steps 1 and 3 of both methods were identical; however, in Step 2 of Method 2, -COOH moieties were derivatized with 10% (v/v) boron trifluoride (BF3) in MeOH or n-butanol (n-BuOH). The BF3/MeOH and BF3/n-BuOH were ineffective at converting species with more than 2-OH moieties. Average standard deviations for derivatization of 36 model compounds by the 3-step methods using TMSD/MeOH and BF3/(MeOH) were 7.4 and 14.8%, respectively. Average derivatization efficiencies for Methods 1 and 2 were 88.0 and 114%, respectively. Despite the lower average derivatization efficiency of Method 1, distinct advantages included a greater certainty of derivatization yield for the entire suite of mono- and multi-functional species and fewer processing steps for sequential derivatization. Detection limits for Method 1 using GC×GC-ToF-MS were 0.3-54pgm-3. Approximately 100 oxygenated organic species were identified and quantified in aerosol filtered from 39m3 of air in an urban location. Levels of species were 0.013-17ngm-3 and were nearly all above the Method 1 limit of detection. © 2015 Elsevier B.V.
Keywords: GC×GC-ToF-MS; Multistep derivatization; Organic aerosol; Oxygenated organics; Secondary organic aerosol